Serotonin is an endogenous regulator of intestinal CYP1A1 via AhR - Christopher Manzella (Nature Portfolio, 2018)
Abstract Aryl hydrocarbon receptor (AhR) is a nuclear receptor that controls xenobiotic detoxification via induction of cytochrome P450 1A1 (CYP1A1) and regulates immune responses in the intestine. Metabolites of L-tryptophan activate AhR, which confers protection against intestinal inflammation. We tested the hypothesis that serotonin (5-HT) is an endogenous activator of AhR in intestinal epithelial cells. Treatment of Caco-2 monolayers with 5-HT induced CYP1A1 mRNA in a time- and concentration-dependent manner and also stimulated CYP1A1 activity. CYP1A1 induction by 5-HT was dependent upon uptake via serotonin transporter (SERT). Antagonism of AhR and knockdown of AhR and its binding partner aryl hydrocarbon receptor nuclear translocator (ARNT) attenuated CYP1A1 induction by 5-HT. Activation of AhR was evident by its nuclear translocation after 5-HT treatment and by induction of an AhR-responsive luciferase reporter. In vivo studies showed a dramatic decrease in CYP1A1 expression and other AhR target genes in SERT KO ileal mucosa by microarray analysis. These results suggest that intracellular accumulation of 5-HT via SERT induces CYP1A1 expression via AhR in intestinal epithelial cells, and SERT deficiency in vivo impairs activation of AhR. Our studies provide a novel link between the serotonergic and AhR pathways which has implications in xenobiotic metabolism and intestinal inflammation.